2020
DOI: 10.1101/2020.09.11.20192849
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors associated with limited access to condoms and sources of condoms during the COVID-19 pandemic in South Africa

Abstract: Background: Evidence have shown that the prescribed lockdown and social distancing due to the novel coronavirus disease 2019 (COVID-19) has made accessing essential health care much more difficult in low-and middle-income countries (LMICs). Access to contraception is essential and should not be denied, even in the time of a global crisis because it is associated with health benefits. It is paramount to maintain timely access to contraception without unnecessary barriers. Hence, this study examines the factors … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…2020) and empirical studies on the impacts of COVID‐19 on SRH have emerged (Gilbert et al. 2021; Bolarinwa 2021; Lewis et al. 2021a; Both, Castle, and Hensen 2021; Yarger et al.…”
Section: Discussionmentioning
confidence: 99%
“…2020) and empirical studies on the impacts of COVID‐19 on SRH have emerged (Gilbert et al. 2021; Bolarinwa 2021; Lewis et al. 2021a; Both, Castle, and Hensen 2021; Yarger et al.…”
Section: Discussionmentioning
confidence: 99%
“…We identified the covariates based on similar studies on family planning [26,30,33,34] and the availability of the variables in the 2018 NDHS dataset. The covariates constitute the second explanatory domain and are included in the analysis to control for possible confounders in the study analytical model.…”
Section: Covariatesmentioning
confidence: 99%
“…27 A similar study from South Africa's shared their experience of covid-19 and reported that there was difficulty to access the supply of condoms during the Covid-19 pandemic especially during the initial days of the pandemic due to lockdown restrictions. 28 The pandemic guidelines of restriction and closer of markets made it difficult to easily availability of contraceptives supply. Reference Reproductive health consultation of couple's, want for family planning was not met properly.…”
Section: The Black Clouds Of Pandemic Over Sexuality and Intimacymentioning
confidence: 99%